2021
DOI: 10.3892/etm.2021.10551
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of the thoracolumbar junction in the process of backward fall: An experimental study and finite element analysis

Abstract: The aim of the present study was to evaluate the biomechanical mechanism of injuries of the thoracolumbar junction by the methods of a backward fall simulation experiment and finite element (FE) analysis (FEA). In the backward fall simulation experiment, one volunteer was selected to obtain the contact force data of the sacrococcygeal region during a fall. Utilizing the fall data, the FEA simulation of the backward fall process was given to the trunk FE model to obtain the stress status of local bone structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The form of a buttock fall was assumed as the boundary condition in this analysis; a total vertical compressive force of 4000 N (100 N/step × 40 steps [13] ) was applied to the upper surface of the model (85% vertebral body and 15% vertebral arch). Regarding stress during falls, a study [13] reported that the maximum impact force of instantaneous stress in vertebrae during a backward fall experiment (in the form of a buttock fall) was 4056 ± 263 N. Thus, standards (4000 N) were adopted. Complete fixation of the lower surface of the vertebral body was performed.…”
Section: Computational Analysesmentioning
confidence: 99%
“…The form of a buttock fall was assumed as the boundary condition in this analysis; a total vertical compressive force of 4000 N (100 N/step × 40 steps [13] ) was applied to the upper surface of the model (85% vertebral body and 15% vertebral arch). Regarding stress during falls, a study [13] reported that the maximum impact force of instantaneous stress in vertebrae during a backward fall experiment (in the form of a buttock fall) was 4056 ± 263 N. Thus, standards (4000 N) were adopted. Complete fixation of the lower surface of the vertebral body was performed.…”
Section: Computational Analysesmentioning
confidence: 99%